INOVAÇÃO TECNOLÓGICA E SUSTENTABILIDADE EM HABITAÇÃO SOCIAL NO SUL DO BRASIL - Kalil, Rosa Maria Locatelli; Gelpi, Adriana; Oliveira, Wagner Mazetto de; Serraglio, Alisson (ENCONTRO NACIONAL DE TECNOLOGIA DO AMBIENTE CONSTRUÍDO, 2018)
The paper addresses the issue of innovation and sustainability in social housing programs(SHP) in the north of Rio Grande do Sul, in the south of Brazil. The main objective is to identify elements of innovation and sustainability in social housing projects in a regional polo municipality. Based on documentary and field surveys, some aspects of technological innovation with the construction of in situ concrete walls are analyzed. As a result, it is observed that the precariousness of urban infrastructure, the distance from the centralities and the difficulty of access to community equipment make social sustainability difficult. However, it is verified in specific case studies of social housing development advances in innovation, in constructive technology in concreting in metallic special forms and in the use of elements of energy efficiency. The results indicate that although the projects only met a few minimum legal criteria and requirements to obtain the licenses and public financing, there was a regular incentive to innovation and sustainability, with attention to specific technical norms of housing development and construction systems.